A mediational analysis of adverse experiences in childhood and quality of life in adulthood. Issue 1 (5th January 2022) - Vederhus, John‐Kåre; Haugland, Siri Håvås; Timko, Christine
Abstract: Objectives: This study examined associations of three prevalent adverse childhood experiences (ACEs) – parents' problematic alcohol use (PPAU), parental separation/divorce, and lack of support from a trusted adult–with adult quality of life (QoL), and potential mediators of associations. Methods: Data were from a representative survey ( N  = 28, 047) in Norway that assessed ACEs, QoL, and potential mediators: enduring perceptions of childhood hardships (Difficult Childhood Questionnaire; DCQ), current mental distress, and current social isolation. Latent regression analyses examined potential mediators. Results: Each ACE was positively associated with perceptions of childhood as difficult (higher DCQ scores). In turn, ACEs were negatively associated with adult QoL through indirect effects. Lack of support from a trusted adult had the strongest negative association with adult QoL, compared to PPAU and parental separation/divorce. The association between the ACEs and QoL was explained through the mediators of mental distress and social isolation. Conclusions: Of the examined ACEs, lack of support from a trusted adult had the strongest negative impact on adult QoL. Adult support to vulnerable children could potentially ameliorate adult consequences of ACEs. In addition, adults reporting difficulties due to childhood adversities may benefit from therapeutic interventions that address both psychological distress and isolation.